Regenerative endodontic procedures in immature permanent teeth with pulp necrosis: Scientific evidence from an integrative review (Research, Society and Development, 2026)
Regenerative endodontic procedures (REPs) have emerged as a biologically oriented alternative in the treatment of immature permanent teeth with pulp necrosis, a condition that compromises root development and increases the risk of fractures. This study aimed to critically analyze the scientific evidence on REPs, with emphasis on their biological foundations, clinical protocols, outcomes, and limitations. An integrative review was conducted in the PubMed, ScienceDirect, and LILACS databases, using English-language DeCS descriptors combined with the Boolean operator AND. Full-text and free articles published between 2021 and 2025 in Portuguese, English, and Spanish were included. The analyzed studies demonstrated that regenerative endodontic procedures (REPs) present favorable clinical results, including increased root length, thickening of dentinal walls, and healing of periapical lesions. However, relevant limitations were evidenced, such as the heterogeneity of clinical protocols, the variability of biological responses, and the absence of consistent histological evidence confirming true pulp regeneration. It is concluded that regenerative endodontic procedures represent a promising and innovative approach, with the potential to promote continuous root development and structural recovery of necrotic immature teeth. However, their consolidation in clinical practice depends on the standardization of protocols and the strengthening of scientific evidence through studies with greater methodological rigor and long-term follow-up.